QUO VADIS DEMOKRASI PROSEDURAL DAN PEMILU : SEBUAH REFLEKSI TEORITIS - Ida Budhiati (Masalah-Masalah Hukum, 2013)
Abstract General election is the one of principle of democracy. It means that democracy in Indonesia manifested through the regulation No. 15 of 2011 about the General Election Commissions who defines the term of democracy within the concept of directly, general, free, sacred, fairness and justice. On realization the concept of democracy, public participation which are the voice of majority really meaningfull. Through general elections will make the newness government formation, in another words, general election is an instition who reproduces a new social contract. To construct on model of the ideal general election is not easy. Independence of general election commission is crucial for democratic election could be run properly. Keywords : democracy, General Election, social contract Abstrak Pemilihan umum merupakan sebuah prinsip dari demokrasi. Arti demokrasi di Indonesia termanifestasikan di dalam UU No. 15 Tahun 2011 tentang Penyelenggara Pemilihan Umum yang mendefinisikan demokrasi dengan rangkaian kata langsung, umum, bebas, rahasia, jujur, dan adil. Dalam mencapai sebuah cita demokrasi, partisipasi rakyat menjadi kunci utamanya dalam penyelenggaraan pemilihan umum, dimana suara mayoritaslah yang menentukan. Melalui pemilihan umum pemerintahan yang baru pun terbentuk, dengan kata lain pemilu merupakan sebuah lembaga yang mereproduksi kontrak sosial baru. Mengkonstruksikan pemilihan umum yang ideal dan demokratis tidaklah mudah. Independensi penyelenggara pemilihan umum sangatlah penting agar pemilihan umum yang demokratis dapat berjalan secara fair. Kata Kunci : demokrasi, Pemilihan Umum, kontrak sosial